Evaluation of fracture on children in orthopaedic and traumatology division in Dr. Wahidin Sudirohusodo Central General Hospital Makassar January 2016-December 2017 - Robin Kurnia Wijaya; Muhammad Nasser Mustari (DiscoverSys Inc., 2020)
Background: Fractures in children can be caused by a long term disability and decreasing quality of life in every people that involved. Factors that affect fractures incidences must be identified so that we can create prevention management. This study aims to evaluate the fractures pattern of children in orthopaedic and traumatology in dr. Wahidin Sudirohusodo Central General Hospital Makassar.Methods: A cross-sectional study was conducted among children under 19 years old by collecting a medical record of patients. The prevalence and patterns of fractures were reviewed for details, such sex, range of age, causes, place of injury, single or multiple fractures, types or location of single fracture, and treatment of fractures. Data were analysed using SPSS version 17 for Windows.Results: There were 152 children in the study, and 72.3% were boys. Most common occur at the 12-18 years age group (92.8%), most of them were caused by traffic accidents (73.6%). Consequently, the location in which fractures were most prevalent was the street (76.9%). Most of them were presented as a single fracture (72.3%) dominated by closed fracture (63.6%), while distal radius/ulna (12.7%) was the most common fracture sites in this study and most patients have undergone surgery for their treatment (84.8%).Conclusion: Most of the patients were boys and caused by traffic accidents. A single and close fracture were the most common types of fracture.